Chronotop Features in Epic and Drama Works - Khursanov Dilshod (International Consortium of Education and Culture Research Studies, 2019)
This article highlights the features of the chronotope in epic and dramatic births. Space and time in a broad and narrow sense, their clarity and uncertainty are analyzed on the scale of literary genera. It is about the meaning of the chronotope in the plot and composition.